Pelatihan Penyusunan Laporan Keuangan Digital Menggunakan Aplikasi Buku Kas Pada Usaha UMKM Miener - Subhi, Ramadhan; Zoniarti, Zoniarti; Yusnita, Yuli; Aprilia, Melisa; Alda, Denada; Saputra, Ilham Giri Muda (Universitas Dehasen Bengkulu, 2024)
The development of technology is very influential on the times, especially in today's digital era. Technology has had a significant impact on human life in the social, economic and cultural fields. In the economic sector, technology changes business processes to be more efficient and effective, thereby increasing productivity and business growth. One of them is the development of micro, small and medium enterprises (UMKM) which are already numerous in Indonesia. The background of the formation of UMKMs in Indonesia is the rapid development of technology, limited access to capital and high unemployment rates which cause poverty. The implementation of this service is carried out by socialising the use of theash book application in Miener UMKM. This community service activity consists of five stages, namely: Identification process, Preparation, Interview, Implementation stage, Evaluation of activity results. Based on the training and socialisation carried out, Miener business owners are very easy to understand and the applications used are very helpful in the process of recording financial reports. The use of applications in the UMKM process is very helpful and simplifies transactions so that there are no errors in the sales transaction process. Recording financial reports provided automatically makes it easy for business owners to understand and is very efficient in its use.